Vaccinated Patients Admitted in ICU with Severe Pneumonia Due to SARS-CoV-2: A Multicenter Pilot Study - Ángel Estella (MDPI AG, 2021)
Background: The aim of this study was to analyze the percentage of patients admitted to the ICU having received the vaccine against COVID-19, to describe the clinical profile of vaccinated patients admitted to the ICU, and to assess the humoral immune response to vaccination. Methods: In this multicenter prospective descriptive cohort study, consecutive critically ill patients with confirmed SARS-CoV-2 pneumonia who received at least one dose of the SARS-CoV-2 vaccine were included. The time of study was from 1 July to 10 August of 2021. Results: Of the 94 consecutive patients from seven Andalusian ICUs admitted during the time of study, 50 (53.2%) received at least one dose of anti SARS-CoV-2 vaccine. No patient was admitted having previously had SARS-CoV-2 infection. The B.1.617.2 (Delta) variant was the most frequently identified, in 80.76% of cases. Patients with a complete vaccination with non-optimal antibody levels were immunocompromised. Fifteen patients were admitted to the ICU with Acute Respiratory Distress Syndrome (ARDS) without having completed their vaccination; the clinical profile was younger and with less comorbidities compared to patients with full vaccination. There were no differences in severity of ARDS. Conclusions: Most of the patients who were admitted to the ICU having received a dose of the vaccine were not optimally vaccinated; fully vaccinated patients who did not obtain optimal serum antibody levels were patients considered immunocompromised.